Effects of varying post-warm-up recovery time on 200-m time-trial swim performance - Zochowski, T.; Johnson, E.; Sleivert, G. G. (International Journal of Sports Physiology and Performance, 2007)
Warm-up before athletic competition might enhance performance by affecting various physiological parameters. There are few quantitative data available on physiological responses to the warm-up, and the data that have been reported are inconclusive. Similarly, it has been suggested that varying the recovery period after a standardized warm-up might affect subsequent performance. Purpose: To determine the effects of varying post-warm-up recovery time on a subsequent 200-m swimming time trial. Methods: Ten national-caliber swimmers (5 male, 5 female) each swam a 1500-m warm-up and performed a 200-m time trial of their specialty stroke after either 10 or 45 min of passive recovery. Subjects completed 1 time trial in each condition separated by 1 wk in a counterbalanced order. Blood lactate and heart rate were measured immediately after warm-up and 3 min before, immediately after, and 3 min after the time trial. Rating of perceived exertion was measured immediately after the warm-up and time trial. Results: Time-trial performance was significantly improved after 10 min as opposed to 45 min recovery (136.80 ± 20.38 s vs 138.69 ± 20.32 s, P < .05). There were no significant differences between conditions for heart rate and blood lactate after the warm-up. Pre-time-trial heart rate, however, was higher in the 10-min than in the 45-min rest condition (109 ± 14 beats/min vs 94 ± 21 beats/min, P < .05). Conclusions: A post-warm-up recovery time of 10 min rather than 45 min is more beneficial to 200-m swimming time-trial performance.